Key Words: Labour Productivity, Potential Product, Capital Stock, Khuzestan The Two-sector Financial Market and its Effects on Investment in Iran Economy - Mahmood Khataei; Roya Seifipoor (فصلنامه پژوهش‌های اقتصادی ایران, 2005)
In Iran, financial market is heavily dominated by the government. The big share of market is owned and run by government, particularly in banking sector. In effect the range of interest rates for different deposits and loans in banks are fixed by Islamic Republic of Iran Central Bank (IRICB). Since the rates are well below the equilibrium levels, selective credit policies are common components of financial restriction in Iran. In other words credit rationing is implemented in official market. Under such circumstances, a black marker for deposits & loans is formed. It operates with very higher interest rates, but very efficient with respect to decision making process.     The two official and non- official (black market) markets form the two – sector financial system of Iran. Each sector is managed with different rules and policies. As a result some well known rules in monetary policy do not work in the expected way in Iran. In particular decreasing interest rate policy in official market does not boost the demand through investment. We show theoretically the subject by a modified version of Loanable Funds Theory for a two – sector financial market. Moreover an estimated Iran investment function confirms empirically the theoretical approach. Engle – Granger Test confirms the results too.     Also financial repression in Iran causes some transfer payments by deposit owners to those receive loans in official market which could be as high as over %10 of GDP. The policy implication to be adopted by policy makers is a well known deregulation policy which results in integration of the two markets.